Drug combination therapy for emerging viral diseases. Issue 10 (October 2021) - Shyr, Zeenat A.; Cheng, Yu-Shan; Lo, Donald C.; Zheng, Wei
Highlights: Effective therapeutics for emerging viral diseases, particularly COVID-19 are critically needed. Combination therapy has been historically successful for chronic viral diseases. Drugs identified through repurposing can rapidly progress to clinical applications. Synergistic drugs combinations may be necessary to effectively combat COVID-19. Abstract: Effective therapeutics to combat emerging viral infections are an unmet need. Historically, treatments for chronic viral infections with single drugs have not been successful, as exemplified by human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections. Combination therapy for these diseases has led to improved clinical outcomes with dramatic reductions in viral load, morbidity, and mortality. Drug combinations can enhance therapeutic efficacy through additive, and ideally synergistic, effects for emerging and re-emerging viruses, such as influenza, severe acute respiratory syndrome-coronavirus (SARS-CoV), Middle East respiratory syndrome (MERS)-CoV, Ebola, Zika, and SARS-coronavirus 2 (CoV-2). Although novel drug development through traditional pipelines remains a priority, in the interim, effective synergistic drug candidates could be rapidly identified by drug-repurposing screens, facilitating accelerated paths to clinical testing and potential emergency use authorizations.